DNA priming for seasonal influenza vaccine: a phase 1b double-blind randomized clinical trial. - Julie E Ledgerwood; Abbie R Bellamy; Robert Belshe; David I Bernstein; Srilatha Edupuganti; Shital M Patel; Phyllis Renehan; Thad Zajdowicz; Richard Schwartz; Richard Koup; Robert T Bailer; Galina V Yamshchikov; et al. (PLoS ONE)
Background The efficacy of current influenza vaccines is limited in vulnerable populations. DNA vaccines can be produced rapidly, and may offer a potential strategy to improve vaccine immunogenicity, indicated by studies with H5 influenza DNA vaccine prime followed by inactivated vaccine boost. Methods Four sites enrolled healthy adults, randomized to receive 2011/12 seasonal influenza DNA vaccine prime (n=65) or phosphate buffered saline (PBS) (n=66) administered intramuscularly with Biojector. All subjects received the 2012/13 seasonal inactivated influenza vaccine, trivalent (IIV3) 36 weeks after the priming injection. Vaccine safety and tolerability was the primary objective and measurement of antibody response by hemagglutination inhibition (HAI) was the secondary objective. Results The DNA vaccine prime-IIV3 boost regimen was safe and well tolerated. Significant differences in HAI responses between the DNA vaccine prime and the PBS prime groups were not detected in this study. Conclusion While DNA priming significantly improved the response to a conventional monovalent H5 vaccine in a previous study, it was not effective in adults using seasonal influenza strains, possibly due to pre-existing immunity to the prime, unmatched prime and boost antigens, or the lengthy 36 week boost interval. Careful optimization of the DNA prime-IIV3 boost regimen as related to antigen matching, interval between vaccinations, and pre-existing immune responses to influenza is likely to be needed in further evaluations of this vaccine strategy. In particular, testing this concept in younger age groups with less prior exposure to seasonal influenza strains may be informative. Trial registration ClinicalTrials.gov NCT01498718.